Teaching Listening Comprehension - Mykhailova, Nelia (My University, 2016)
The article analyses the experience of listening comprehension that is concerned with decoding of a speech, which involves continual mental processing, concentrated attention, and memory. In other words it represents a perceptive and mental mnemonic activity.
Keywords: аудіювання; listening; декодуванням мовлення; decoding speech; перцептивна діяльність; perceptual activity; кафедра іноземних мов професійного спрямування